PHYSICOCHEMICAL AND RHEOLOGICAL CHARACTERIZATION OF AVOCADO OILS - Jorge, Tamara de Souza [UNESP]; Polachini, Tiago Carregari [UNESP]; Dias, Liara Silva [UNESP]; Jorge, Neuza [UNESP]; Telis-Romero, Javier [UNESP] (Univ Federal Lavras-ufla, 2015)
Avocado oil is rich in bioactive compounds, which can improve human health by acting as an antioxidant. It may be extracted from different varieties of avocado, such as Margarida and Hass varieties, each of them with particular characteristics. Aiming to evaluate the differences between them, avocado fruits and pulps from these were analyzed according to their physicochemical characteristics. After extracted, the oils had their bioactive characteristics studied and rheological behavior determined through a rotational rheometer. They were then compared to commercial avocado oil. The fruits of Margarida variety had greater size, higher weight (664.51 g), and higher pulp yield (72.19%) than Hass variety, which showed higher lipid content (65.29 g/100 g dry basis). The commercial oil showed less primary oxidative degradation, whereas Margarida variety had a lower level of secondary degradation products as well as a higher content of bioactive compounds, such as phytosterols (999.60 mg/kg) and tocopherols (36.73 mg/kg). The rheological behaviors of both oils were appropriately described through Newton model, with R-2 > 0.999 for all temperatures. By an Arrhenius type equation, it was verified that Hass's rheological parameters are more influenced by temperature than Margarida and commercial oil, presenting activation energy of 33.6 kJ/mol.
Keywords: Margarida; Hass; fatty acids; newtonian fluid; Arrhenius